Unravelling the ambiguous reproductive biology of paspalum malacophyllum : a decades old story clarified - Hojsgaard, Diego Hernán (2015)
Fil: Hojsgaard, Diego Hernán. Universidad de Gotinga. Departamento de Botánica Sistemática; Alemania.